The Many-faced Fandom: _Cesuo_'s Collective Persona on Weibo - Yang, Yifei (AoIR Selected Papers of Internet Research, 2026)
In the current era of greatly increased availability of media technology platforms, fans with their domains continue to expand, becoming a rapidly growing concept of our time (Scott, 2019; Stanfill, 2019). The study examines $2 [厕所, toilet], a type of social bot account on Weibo, differs from algorithm-driven bots as it’s manually managed by real users who set up site conventions, review and post users’ submissions, and promote opinion coordination. As an emerging mode of information exchange and group interaction in Chinese Internet culture, $2 is especially active in fandom. It serves as both an organizational structure and an information dissemination tool, offering insights into how individual fans regulate collective personas and providing a new organizational model for fan communities in the platform media era. $2 can be seen as a type of fan-create Nonhuman Online Persona (NHOP), a coherent digital assemblage with no direct connection to individual human identities. The research investigates how Cesuo operates, its role in fan community building, and the power dynamics it establishes. By analyzing two representative $2 accounts and conducting semi-structured interviews, the study identifies three key characteristics of $2 : its anonymity and collective identity performance, its usage of fan slang as a form of community regulation, and its paratextual production and emotional bonding. Ultimately, the study argues that $2 enables alternative forms of digital fandom, emphasizing emotional connection and shared agency over individualized fan identity.